Smooth coronal surface, resin restoration and microleakage. - (:unkn) unknown (My University, 1997)
The space between the resin and the cavity walls has always become interesting to search. The aim of this study was to evaluate any differences on leakage values of Class 5 type resin restorations prepared on surrounding surfaces of the tooth crown. Ninety human teeth were prepared as Class 5 cavities on buccal, lingual, mesial and distal surfaces and were randomly divided into groups for bevelling, groove preparation and as control. The subgroups were arranged as fluoride gel and/or sealant applications. Fluoride gel was applied following the cavity preparations. Sealant was applied over composite resin restorations. Treated teeth were thermocycled and immersed into dye solution for 96 hours. The restorations were evaluated in a stereo-microscope following the sectioning. Bevelling of the cavosurfaces and/or preparation of a groove addition to cavity procedures did not make any difference on the microleakage scores of the restorations done on either surfaces statistically.